Communication Technician: One of the Roles of Yehonala School Public Relations in Maintaining Image - Andy Andy; Angel Purwanti (COMMENTATE: Journal of Communication Management, 2021)
School is one of the institutions in transferring the balance between moral values to students in the learning process, so as to create innovations to improve the quality of institutions nationally. Yehonala School, one of the schools in Batam City that focuses on developing and shaping the characteristics of educators. Yehonala School is a National Plus based school in partnership with Cambridge University Press, and the motto is 'To Grow in Wisdom!' starting from the Play Group level, Elementary School (SD), Junior High School (SMP), High School (SMA) and Vocational High School (SMK). Yehonala School has an image as "The Best Learning Place for Children", the image is obtained through superior programs and achievements obtained from the Indonesia Achievement Center (IAC). The image that has been formed and attached to the Yehonala school in Batam City. This, of course, cannot be separated from the role of Yehonala School's Public Relations in maintaining that image first during the current pandemic. This research is based on an analysis of systems theory and the concept of the four roles of Public Relations proposed by Cutlip, Center and Broom. The type of research applied in this research is descriptive qualitative, the data collection applied in this research is in-depth interviews. The analytical method applied in this research is the Miles and Huberman analysis technique called the interactive model. The purpose of this study was to find out how the role of PR as a communication technician in maintaining an image during a pandemic. The results of the study found that three coding findings related to the role of Yehonala School's Public Relations as a communication technician, namely: (1) Utilization of Social Media (2) Social Media Content (3) The resulting reaction. The role of Yehonala school's PR is only as a communication technician and Yehonala's school implements a closed system because PR does not act as an information seeker.